EUS-Guided Biliary Drainage: A Review Article - Artifon, Everson L A; Ferreira, Flávio Coelho; Otoch, José Pinhata; Rasslan, Samir; Itoi, Takao; Perez-Miranda, Manuel (JOP. Journal of the Pancreas, 2012)
Context To demonstrate a comprehensive review of published articles regarding EUS-guided biliary drainage. Methods Review of studies regarding EUS-guided biliary drainage including case reports, case series and previous reviews. Results EUS-guided hepaticogastrostomy, choledochoduodenostomy and choledochoantrostomy are advanced procedures on biliary and pancreatic endoscopy and together make up the echo-guided biliary drainage. Hepaticogastrostomy is indicated in cases of hilar obstruction, while the procedure of choice is choledochoduodenostomy in distal lesions. Both procedures must be done only after unsuccessful ERCP. The indication of these procedures must be made under a multidisciplinary view while sharing information with the patient or legal guardian. Conclusion Hepaticogastrostomy and choledochoduodenostomy are feasible when performed by endoscopists with expertise in biliopancreatic endoscopy and advanced echo-endoscopy and should be performed currently under rigorous protocol in educational institutions.